Penerapan Digitalisasi Camera Analytic Guna Meningkatkan Tingkat Kepatuhan Driver Dan Menurunkan Tingkat Kecelakaan Dump Truck (DT) Di Jalan Hauling Batubara PT. XYZ - Bakhtiar Rusandi; Taharuddin (JURNAL BISNIS DAN PEMBANGUNAN, 2025)
Abstract: This research aims to determine the effectiveness of implementing digitalization of PT Then, find out the effect on the accident rate after the accident on PT XYZ Hauling Road. This research uses a qualitative approach with a focus on the implementation of digitalization to increase the level of driver compliance and reduce the level of DT accidents on the PT XYZ hauling road. Data was collected through interviews, observation, documentation studies, and analyzed using the Miles and Huberman model. The results shows that the implementation of camera analytic digitization had a good impact to one of contractors PT XYZ, which is implementing digitalization of camera analytic has been an increase the level of compliance, that shown by decrease the number of violations regarding to overspeed up to 81%. And then, the Incident Frequency Rate (TIFR) from initially above the threshold, namely 13.29, can gradually decrease to 6.16 to below the threshold (7.17) with a decrease of 54%.